Contraction Phase and Force Differentially Change Motor Evoked Potential Recruitment Slope and Interhemispheric Inhibition in Young Versus Old - Ermer, Elsa; Harcum, Stacey; Lush, Jaime; Magder, Laurence S.; Whitall, Jill; Wittenberg, George F.; Dimyan, Michael A. (Frontiers in Human Neuroscience, 2020)
Interhemispheric interactions are important for arm coordination and hemispheric specialization. Unilateral voluntary static contraction is known to increase bilateral corticospinal motor evoked potential (MEP) amplitude. It is unknown how increasing and decreasing contraction affect the opposite limb. Since dynamic muscle contraction is more ecologically relevant to daily activities, we studied MEP recruitment using a novel method and short interval interhemispheric inhibition (IHI) from active to resting hemisphere at 4 phases of contralateral ECR contraction: Rest, Ramp Up (increasing at 25% of maximum voluntary contraction (MVC)), Execution (tonic at 50% MVC), and Ramp Down (relaxation at 25% MVC) in 42 healthy adults. We analyzed the linear portion of resting extensor carpi radialis (ECR) MEP recruitment by stimulating at multiple intensities and comparing slopes, expressed as mV per TMS stimulation level, via linear mixed modeling. In younger participants (age≤30), resting ECR MEP recruitment slopes were significantly and equally larger both at Ramp Up (slope increase=.047, p<.001) and Ramp Down (slope increase=.031, p<.001) compared to rest, despite opposite directions of force change. In contrast, Active ECR MEP recruitment slopes were larger in Ramp Down than all other phases (Rest: .184, p<.001; Ramp Up: .128, p=.001; Execution: p=.003). Older (age≥60) participants’ resting MEP recruitment slope was higher than younger participants across all phases. IHI did not reduce MEP recruitment slope equally in old compared to young. In conclusion, our data indicate that MEP recruitment slope in the resting limb is affected by the homologous active limb contraction force, irrespective of the direction of force change. The active arm MEP recruitment slope, in contrast, remains relatively unaffected. Older participants had steeper MEP recruitment slopes and less interhemispheric inhibition compared to younger participants.